REFUSAL STRATEGIES USED BY MALE AND FEMALE SELLERS AT PASAR RAYA PADANG - Rosa, Rusdi Noor (English Department FBS UNP, 2010)
This article is aimed at finding different strategies used by male and female sellers while refusing the buyers’ offer. This study was done by using descriptive research design in which the data related to the object of the study were collected to answer the research question. The data of this study are refusals in the bargaining process between sellers and buyers that took place in Pasar Raya Padang. The finding of the research shows that male sellers used non performative statement strategy most frequently which implicitly indicated that they tended to refuse the buyers’ offer in a direct way. Female sellers, on the other hand, used excuse, reason, and explanation strategy most frequently which indicated that they preferred to refuse their buyers’ offer in an indirect way.